Literature Review: Neuromuscular Taping and Exercise for Diabetes Mellitus - Zulikha, Nora Eny; Rahayu, Umi Budi; Haqi, Nadyastama Faisal (Universitas Muhammadiyah Surakarta, 2026)
Introduction: This literature review study was motivated by global health challenges such as diabetes mellitus (DM), which has become a significant global health issue, particularly in Indonesia, which ranks seventh in the world. Complications from DM, such as diabetic neuropathy, drastically affect patients' quality of life. Non-pharmacological approaches, such as neuromuscular taping therapy (NMT) and physical exercise, can reduce the risk of complications and thus be an effective additional solution in DM management. Methods: The literature review method was applied to five articles obtained from several databases, namely ResearchGate and Google Scholar. The search keywords for articles included NMT, Exercise, and Diabetes Mellitus. The researchers used